PENINGKATAN KAPASITAS PEMERINTAH DESA DALAM PENGELOLAAN KEUANGAN DESA SUNGAI PINANG KECAMATAN PUJUD KABUPATEN ROKAN HILIR - Amri, Pahmi (WEDANA: Jurnal Kajian Pemerintahan, Politik dan Birokrasi, 2019)
Village government is the administration of government affairs and the interests of local communities in the NKRI government system (Law Number 6 of 2014 concerning Villages Article 1 Paragraph (2)). The village head as the organizer of the village government is directly elected by the community through the election of the village head (Law Number 6 of 2014 Article 34 paragraph 1). The village head in village administration is assisted by village officials, namely the village secretary and other village officials. "BPD is located as an element of village administration, functions to determine village regulations with the village head, to accommodate and channel the aspirations of the community". In this case the problems that occur are about Village Wealth Management Procedures, which are more focused on village financial management. The problems that often occur in Sungai Pinang Village, Pujud District, Rokan Hilir Regency are; 1) The many original assets of Sungai Pinang Village can be used as a source of original village income to improve development and the standard of living of the community, especially in Sungai Pinang Village. 2) The many residents of Sungai Pinang Village community who do not yet know about the procedures for managing village wealth. Referring to the above problem, the formulation of the problem in this service is how to increase the capacity of the village government in financial management of Sungai Pinang Village, Pujud River District, Rokan Hilir Regency. The purpose of this service is so that the Device and Community of Sungai Pinang Village, Pujud District, Rokan Hilir Regency can find out and improve the capacity of the village government in managing village finances. The benefits of this service are for lecturers for lecturers, the increase of students' knowledge and knowledge about the Government's Capacity Building in Village Financial Management Sungai Pinang Village, Pujud Rokan Hilir District, For Higher Education, the achievement of darma chess from universities in Riau Islamic University. one of them is community service. For the Community, so that the community can know clearly about Capacity Building of Village Governments in Village Financial Management. The target of community service is to increase awareness of the village government and the community the importance of understanding the Capacity Building of Village Governments in Village Financial Management to realize the Target Development. The location of this community service activity is Sungai Pinang Village, Pujud District, Rokan Hilir Regency. This village is approximately 7 hours drive from the city of Pekanbaru. The timing of this activity is carried out on Saturdays. December 28, 2018 at 09.00 WIB until Completed. The method of implementation is carried out with assistance and question and answer with the community and village officials. Furthermore, the Dedication Team will conduct a direct review of the documents that are in the Village archive to see the shortcomings. The material presented in this service is Law no. 6 of 2014 and supporting material.